Comparison occlusion between closed and open reduction of unilateral condylar fractures: a randomized controlled trial - Sirimaharaj, Wimon; Kwan-ngern, Krit; Boonyawong, Pattriyaporn (Biomedical Sciences and Clinical Medicine, 2017)
Objective To compare occlusion, outcome and complications with the closed method versus the open method of treatment for unilateral mandibular condylar fracture. Methods Twenty patients with unilateral mandibular condylar fractures (neck or subcondyle) of the mandible were evaluated. The patients were randomly divided into two groups, with group 1 receiving closed reduction and group 2 receiving open reduction and internal fixation. Patients were followed up for a period of 3 months. Results No statistically significant differences between the open and closed treatment methods were found in terms of occlusion, interincisive distance, temporomandibular joint (TMJ) pain, TMJ clicking and period of hospital stay. Statistically significant improvement was seen in group 2 compared with group 1 in terms of chin deviation on mouth opening. Group 1 had shorter operation times and less postoperative pain scores than group 2. None of the Group 2 patients developed permanent facial nerve damage or unsightly scarring. Conclusions There is no statistically significant difference between the two methods in terms of occlusion. A statistically significant difference was seen in the patients treated with the open method, with improved chin swaying compared with those treated with the closed method.